THE PLACE OF RESTRICTIVE MEANS IN THE SYSTEM OF CRIMINAL LAW MEASURES - Novikova, Kateryna (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Purpose: to determine the place of restrictive means and to establish their relationship with other means of criminal law. The methodological basis of the study is the dialectical method, which provided an opportunity to consider the studied phenomena in the development and relationship, unity and contradictions; system-structural method was used in the study of restrictive means in the system of criminal law; the dogmatic method was used to clarify the meaning of terms contained in regulations and used in legal doctrine and others. Results: restrictive means occupy a certain place in the classifications of legal means. First, the restrictive means relate to the means of installation. In addition, they are essentially more coercive than encouraging, so they are coercive measures. Further, restrictive means are non-punitive means because they do not meet the purpose of punishment. Finally, in the system of multi-track means of criminal law, restrictive means are security measures. Regarding the ratio of restrictive means with criminal liability, it can be noted that they do not meet the criteria of criminal liability, but belong to other means of criminal law. Discussion of problems of determining the place of restrictive means in the system of means of criminal law. The above gives grounds for the following conclusions. First, it is noteworthy that the legislator does not comply with the requirements of a systematic approach in formulating the provisions of criminal law. In particular, the norms of the same institute of other measures of criminal law nature are scattered by him in sections XIV, XIV1, XV, and now also XIII1 of the General Part of the Criminal Code of Ukraine. Obviously, it would be more reasonable and convenient to bring them all together in one section. Secondly, when applying restrictive measures, courts must assume that they are not criminal liability, but belong to other measures of a criminal law nature. Therefore, they should be applied according to the rules established in the Criminal Code of Ukraine for other measures, and not for criminal liability or its individual elements.